Nursing tutors' perception of clinical supervision skills - Silva, Ernestina (2016)
Abstract Introduction: The evolution of science and technology, changes within the healthcare organizations and new healthcare emerging philosophies require an active participation from healthcare professionals in helping in their peers’ training. The supervision process is therefore more and more important. Objectives: To identify specialist nursing instructors’ perception of the clinical supervisor skills in child-health area and paediatrics. Material and methods: Qualitative-descriptive and phenomenological study composed by a sample of ten nursing tutors in the Dr. Nélio Mendonça Hospital’s Paediatrics Department. We used a semi-structured interview and recordings of the conversations. We performed a content analysis on the corpus of all the interviews, once we had denied subcategories and indicators. Results: The category “clinical supervisor skills” emerged from our study and the subcategories which were the most commonly referred were “personal characteristics with a 38% record unit and “professional skills” (25.7%). As far as the relevant aspects in the child-health area and paediatrics are concerned, personal and professional skills stood out once again, with a 40.4% rate each. The main facilitating factor in the supervision process was the fact that it is a structured process (21.6%), and the inhibition factor was the deficit that exists in interpersonal relationships (21.7%). Globally, there were more record units associated with inhibition factors. Conclusion: Knowing what supervisors’ insights in such a specific area as child-healthcare and paediatrics are, we think that this study can be a contribution to improve the quality of the supervision process in nursing. A joint effort between supervisor and supervised nurse will be needed to improve the processes that link institutions and their actors, processes where knowledge, experiences and professional objectives are commonly shared.